2016
DOI: 10.1021/acs.jpcc.5b10918
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Sum Frequency Generation Spectroscopy of Fullerene at Dielectric Interfaces

Abstract: Vibrational sum frequency generation (VSFG) spectroscopy was used to measure the interfacial spectra of fullerene thin films on dielectric substrates that are commonly used in IR spectroscopy. The VSFG spectra on SiO2 and CaF2 exhibit notably different intensities for the F1u and Ag vibrational modes. This difference is attributed to different interfacial surface charges and C60/surface interactions. DFT calculations were performed to model the influence of a unidirectional electrostatic perturbation on the IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
2
21
0
1
Order By: Relevance
“…SFG has been applied to study polythiophene molecular orientations at interfaces. , Here, we focused on elucidation of molecular structures at the buried polythiophene/graphene interfaces, and the correlations between the PT side-chain length and the molecular orientation of the PT thiophene backbone at such interfaces using SFG. We compared the interfacial thiophene backbone orientations at the PT/graphene interfaces to those at the PT/CaF 2 interfaces, as well as the PT/perovskite interfaces that were reported previously .…”
Section: Introductionmentioning
confidence: 99%
“…SFG has been applied to study polythiophene molecular orientations at interfaces. , Here, we focused on elucidation of molecular structures at the buried polythiophene/graphene interfaces, and the correlations between the PT side-chain length and the molecular orientation of the PT thiophene backbone at such interfaces using SFG. We compared the interfacial thiophene backbone orientations at the PT/graphene interfaces to those at the PT/CaF 2 interfaces, as well as the PT/perovskite interfaces that were reported previously .…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the molecular orientation of such functional groups is achieved by controlling the polarization of each incoming beam as well as the generated SFG beam. Recent progress in SFG research has shown that SFG is a powerful tool to investigate surfaces and interfaces of many systems such as biological systems, organic molecules, , and water surface/interfaces , as well as organic semiconductor materials. The research reported in this article aims to understand the correlation between the structure of polythiophene (PT) at the buried perovskite/polythiophene (PT) interface in a solar cell and the solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Sohrabpour et al showed that SFG can also be used to study fullerene thin films on dielectric substrates. Fullerene is one of the most commonly used acceptor materials in OPV devices, and SFG has been able to study fullerene interfacial structures, which proved SFG has the capability to study not only donor materials but also acceptor materials . SFG study on electronic structures at buried interfaces also demonstrated that SFG is a powerful interface sensitive tool that can be used to study these structures in organic semiconductors, as reported by Li et al As stated before, most progress still focuses on OFETs so far, but these two studies have demonstrated that SFG can have a broader impact in elucidating interfacial properties in OPVs and OLEDs devices in situ.…”
Section: Applications Of Sfg To Study Polymer Surfaces and Interfacesmentioning
confidence: 83%